Diversification of income sources for cocoa farm households: a case study of the Central West of Côte d'Ivoire. (2016) - Iritié, Bi Goli Jean Jacques; Djaléga, Fabrice Soukou
This paper is aimed at identifying complementary sources of income for cocoa farm households in the Central West of Côte d'Ivoire. Our methodology consists of four successive stages: 1) a need assessment of cocoa households and specificities of the study area through a participatory diagnosis in order to propose potential income generating activities; 2) a technical qualitative analysis of these activities; 3) an analysis of the profitability; 4) an analysis of their social acceptability. It appears that beekeeping and snail breeding is the most appropriate activities for this cocoa producing region. However, the results show that the lack of information and technical knowledge, the religious burdens and the high local illiteracy rate can constitute barriers to the implementation of IGAs. Finally, as future prospects, we discuss the opportunity to combine horizontal diversification and vertical diversification (especially cocoa processing) in order to give more added value to the sustainable cocoa production and to contribute to the industrial development of Ivorian economy.